Painter and place: Joseph Wright and Derby 1797-1886 - Insley, Alice Amelia (2017)
As the endurance of Wright’s soubriquet ‘of Derby’ shows, the association between Wright and Derby is distinctive in its ongoing cultural resonance. The legacy of this today is the Joseph Wright Collection at Derby Museum and Art Gallery – the largest collection of his work in the world. This thesis is, therefore, concerned not with arguing for the relationship between Wright and Derby but with attending to how it has been represented and claimed during the 19th-century. This will encompass both how the relationship influenced Wright’s posthumous reputation and how it was enlisted in Derby as the painter was incorporated into the town’s social and cultural fabric. The different claims made upon the artist’s life and locality will become apparent through this, demonstrating the changing relation between painter and place as it was adapted and appropriated according to different times, places, and discourses. This refurbishment of the painter throughout the 19th-century is significant as it provided cultural continuity at a time when the town was rapidly transforming.